Triazole-induced drought stress amelioration on growth, yield, and pigments composition of Helianthus annuus L. (sunfl ower) - Robert, Gabriel Amalan; Paramasivam Manivannan, Mahalingam Rajasekar, (International Multidisciplinary Research Journal, 2016)
In this investigation, a pot culture experiment was conducted to estimate the ameliorating effect of drought stress and drought with triazole compounds (hexaconazole, propiconazole, and tebuconazole) response on growth analysis, pigment composition, and yield parameters of Helianthus annuus L. (Sunflower). Sunflower is one of the most important oil crops and due to its high content of unsaturated fatty acids and a lack of cholesterol, the oil benefits from a desirable quality. Plant growth and productivity are unfavorably affected by nature’s wrath in the form of various biotic and abiotic stress factors. Water deficit is one of the major abiotic stresses, which adversely affects crop growth and yield. Drought stress during vegetative phase, flowering or seed filling period causes considerable decreases in yield and oil content of sunflower. These changes are mainly related to altered metabolic functions, one of those is either loss of or reduced synthesis of photosynthetic pigments and biochemical modifications. From 30 days after sowing (DAS), the plants were subjected to 4 days interval drought stress and drought with triazole compounds and daily irrigation kept as a control. The plant samples were collected on 40, 50, and 60 DAS. Growth, yield parameters, and pigment variations were analyzed. Drought stress decreased growth, yield, and pigments composition chlorophyll, carotenoid, and anthocyanin when compared to control. The triazole ameliorated drought stress by increasing the growth and biochemical potentials and bring into being the way for overcoming drought stress in H. annuus L. plants.